2012
DOI: 10.1016/j.jcf.2011.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and impact on FEV1 decline of chronic methicillin-resistant Staphylococcus aureus (MRSA) colonization in patients with Cystic Fibrosis

Abstract: In our center the prevalence of MRSA in CF patients, chronically colonized with S. aureus and over the age of 4 years, was 15.2% (12.6% chronic infection). MRSA colonization was shown to be associated with a genotype F508del, presence of bronchiectasis and hospitalization. Our spirometric data also show that a MRSA episode entails an FEV(1) decline that is almost double that predicted for CF patients who can remain unaffected by MRSA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
60
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(64 citation statements)
references
References 19 publications
2
60
1
1
Order By: Relevance
“…In 2009 the prevalence of any S. aureus isolate from the respiratory tract of CF patients in USA was 65.8%, of which 23.7% were MRSA [19,20]. A recently published Belgian study reported 67% of their patient population as chronically infected with S. aureus and 18% harboring MRSA strains [21]. This is in contrast to findings in our patient population with only 0.3% of patients harboring MRSA strains and none with chronic MRSA infection.…”
Section: Discussioncontrasting
confidence: 72%
“…In 2009 the prevalence of any S. aureus isolate from the respiratory tract of CF patients in USA was 65.8%, of which 23.7% were MRSA [19,20]. A recently published Belgian study reported 67% of their patient population as chronically infected with S. aureus and 18% harboring MRSA strains [21]. This is in contrast to findings in our patient population with only 0.3% of patients harboring MRSA strains and none with chronic MRSA infection.…”
Section: Discussioncontrasting
confidence: 72%
“…Recent data suggest that MRSA strains are markers of more severe disease in CF patients but are not more virulent than MSSA strains . Acquisition of MRSA has been associated with hospitalization, the F508del genotype and the presence of bronchiectasis [116]. For treatment of S. aureus, recommended drugs, doses and regimens are given in Table 2.…”
Section: S Aureusmentioning
confidence: 99%
“…22 Similar findings have been reported by others. [224][225][226] In addition, MRSA has also been associated with increased mortality; in a cohort study of 19,833 individuals reported to the CFFPR with at least 2 years of follow-up, those with MRSA had a 1.27 higher risk of death when adjusted for severity of disease. 23…”
Section: Iiia3 Other Gram-negative Bacteriamentioning
confidence: 99%